PERANCANGAN SISTEM PENGUKURAN JARAK DENGAN STEREOVISION - Harits Al Furqon Akbar; Adharul Muttaqin; Raden Arief Setyawan (Jurnal Mahasiswa TEUB, 2023)
Stereo vision has become an attractive topic research in the last decades. Many implementations such as theautonomous car, 3D movie, 3D object generation, are produced using this technique. The advantages of usingtwo cameras in stereo vision are the disparity map between images. Disparity map will produce distanceestimation of the object. Distance measurement is a crucial parameter for an autonomous car. The distancebetween corresponding points between the left and right images must be precisely measured to get an accuratedistance. One of the most challenging in stereo vision is to find corresponding points between left and right images (stereo matching). This paper proposed distance measurement using stereo vision using Semi-Global Block Matching algorithm for stereo matching purpose. The object is captured using a calibrated stereo camera. The image pair then looks for the same Point of Interest to make it a measurement parameter. Theimplementation results of this algorithm are furthermore converted to a metric unit for distance measurement. The result shows that the stereo vision distance measurement using Semi-Global Block Matching gives a goodresult. The obtained best result of this work contains error of less than 0,19% for 1,2m distance. Keyword: Distance Measurement, Stereo Vision, Semi-Global Matching